A hatalom és az identitás torz alakzatai: (Szabó Róbert Csaba: Alakváltók) - Béres, Norbert (Studia Litteraria, 2022)
The article explores the ways Róbert Csaba Szabó’s novel Alakváltók (“Shapeshifters”) represents Romania’s 20th century history, with special respect to the regime change in 1989. Accordingly, I link the motifs of “shapeshifting” and metamorphoses to the novel’s desillusionary view on the prospects of political change and transformation in Eastern Europe. Focusing on the central character of Rajnai/Perjovschi, I conclude that the story of his life displays at the micro level what totalitarian power attempts to achieve at the macro level: the disfigurement, concealment or total eradication of personal and group identities.